2022
DOI: 10.1038/s41598-022-15129-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygenation and body mass index association with cognitive function in chronic kidney disease patients without dialysis: a longitudinal study

Abstract: In chronic kidney disease (CKD) patients, the prevalence of cognitive impairment increases with CKD progression; however, longitudinal changes in cognitive performance remain controversial. Few reports have examined the association of cerebral oxygenation with cognitive function in longitudinal studies. In this study, 68 CKD patients were included. Cerebral regional oxygen saturation (rSO2) was monitored. Cognitive function was evaluated using mini-mental state examination (MMSE) score. Clinical assessments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(75 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, our results support the findings of most other studies [ 9 , 14 , 31 ] indicating that eGFR is a risk factor for CFI in patients with CKD. Additionally, the incidence of CFI increased with decreasing eGFR, which is consistent with previous findings [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our results support the findings of most other studies [ 9 , 14 , 31 ] indicating that eGFR is a risk factor for CFI in patients with CKD. Additionally, the incidence of CFI increased with decreasing eGFR, which is consistent with previous findings [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, consistent with the findings of earlier research, a BMI of 30 or above was considered a protective factor in preventing the occurrence of CFI in patients with CKD. As the studies shown that, BMI was positively associated with cognitive function in patients with CKD [ 32 ], and the risk of dementia decreased with BMI increased, whereas the risk increased with underweight [ 49 ]. These previous studies, despite some conflicting results, indicate that CFI in patients with CKD is caused by multiple influencing factors that interact and may enhance or weaken certain mechanisms of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4773 publications were identified at the three electronic databases in the initial search, and 50 studies [ 12 15 , 21 65 ] were included according to the selection criteria. Fig 1 represented the flowchart of the selection of studies for our systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%